TBX2 expression is regulated by PAX3 in the melanocyte lineage. (21st November 2012) - Liu, Fang; Cao, Juxiang; Lv, Jinghu; Dong, Liang; Pier, Eric; Xu, George X.; Wang, Rui‐an; Xu, Zhixiang; Goding, Colin; Cui, Rutao
Summary: The paired box homeotic gene 3 (PAX3) is a crucial regulator for the maintenance of melanocytic progenitor cells and has a poorly defined role in melanoma. To understand how PAX3 affects melanocyte and melanoma proliferation, we identified potential PAX3 downstream targets through gene expression profiling. Here, we identify T‐box 2 (TBX2), a key developmental regulator of cell identity and an antisenescence factor in melanoma, as a directly regulated PAX3 target. We also found that TBX2 is involved in the survival of melanoma cells and is overexpressed in some melanoma specimens. The identification of TBX2 as a target for PAX3 provides a key insight into how PAX3 may contribute to melanoma evolution and may provide opportunities for prosenescence therapeutic intervention aimed at disrupting the ability of PAX3 to regulate TBX2.